2008
DOI: 10.1136/hrt.2007.116715
|View full text |Cite
|
Sign up to set email alerts
|

Gender influence on the diagnostic accuracy of 64-slice multislice computed tomography coronary angiography for detection of obstructive coronary artery disease

Abstract: Objective: To compare the diagnostic accuracy of 64-slice multislice computed tomography (MSCT) coronary angiography between female and male patients using conventional coronary angiography as the reference standard. Design: Diagnostic accuracy study. Setting: University hospital. Patients: 103 consecutive patients (51 men, 52 women, mean (SD) age 60 (10) years) with known and suspected coronary artery disease underwent 64-slice MSCT. Main outcome measures: Diagnostic accuracy of 64-slice MSCT to detect obstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 19 publications
(12 reference statements)
1
35
0
3
Order By: Relevance
“…42,43 In a series of 51 women and 52 men, the diagnostic sensitivity and specificity was similar by sex at 85% and 99%, respectively. 44 An important limitation for CTA is the ionizing radiation that should be used cautiously in younger women because of a heightened lifetime risk of cancer. Contemporary techniques and protocols that are optimized for decrease in radiation exposure should be used in symptomatic women at risk for CAD.…”
Section: Cac Scoring and Ct Angiographymentioning
confidence: 99%
“…42,43 In a series of 51 women and 52 men, the diagnostic sensitivity and specificity was similar by sex at 85% and 99%, respectively. 44 An important limitation for CTA is the ionizing radiation that should be used cautiously in younger women because of a heightened lifetime risk of cancer. Contemporary techniques and protocols that are optimized for decrease in radiation exposure should be used in symptomatic women at risk for CAD.…”
Section: Cac Scoring and Ct Angiographymentioning
confidence: 99%
“…While one study showed lower specificity, 28 another showed lower accuracy and higher rates of nondiagnostic exams. 29 Other studies have shown no difference in accuracy, including ACCURACY multicenter trial (Assessment by Coronary Computed Tomographic Angiography of Individuals Undergoing Invasive Coronary Angiography).…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence for the differences due to safety and efficacy of either imaging modality among both genders is not adequate (8,33). In a cohort of 103 subjects (51 women and 52 men), the diagnostic sensitivity and specificity of coronary CTA was similar by gender at 85% and 99%, respectively (34). In the ACCURACY (Assessment by Coronary Computed Tomographic Angiography of Individuals Undergoing Invasive Coronary Angiography) study, coronary CTA revealed a sensitivity and specificity for demonstration of >50% stenosis of 95% and 83% and for >70% stenosis of 94% and 83% (35).…”
Section: Anatomic Modalitiesmentioning
confidence: 99%